2020
DOI: 10.1152/japplphysiol.00314.2020
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber typology is associated with the incidence of overreaching in response to overload training

Abstract: The aim of this study was to identify markers of training stress and characteristics of middle-distance runners related to the incidence of overreaching following overload training. Twenty-four highly-trained runners (n=16 male; VO2peak=73.3(4.3) mL·kg·min-1; n=8 female, VO2peak=63.2(3.4) mL·kg·min-1) completed 3 weeks of normal training (NormTr), 3 weeks of high-volume training (HVTr; a 10, 20 and 30% increase in training volume each successive week from NormTr), and a 1-week taper (TapTr; 55% exponential red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 75 publications
1
18
2
Order By: Relevance
“…The training was periodized in a way that 2 intensive weeks were followed by 1 recovery week. The training volume progression was similar to previous studies ( 7 , 25 ): during intensive weeks, it increased by 10% compared with the baseline level (2 first weeks of PREP). To ensure sufficient recovery, training volume was always decreased by 25% after 2 intensive weeks ( 26 ).…”
Section: Methodssupporting
confidence: 87%
“…The training was periodized in a way that 2 intensive weeks were followed by 1 recovery week. The training volume progression was similar to previous studies ( 7 , 25 ): during intensive weeks, it increased by 10% compared with the baseline level (2 first weeks of PREP). To ensure sufficient recovery, training volume was always decreased by 25% after 2 intensive weeks ( 26 ).…”
Section: Methodssupporting
confidence: 87%
“…The majority of training intervention studies demonstrate that considerable variability in adaptation to a given exercise stimulus is the norm [e.g., [115][116][117]. The principle of individualization refers to the notion that training prescription must be adapted and optimized according to individual predispositions (performance level, training status/age, sex, recovery/injury status and physiological and structural/mechanical profiles) to maximize the effect and avoid non-responder outcomes [13,52,58,98,118]. Total training load is typically higher in well-trained adult runners of higher performance standard compared to their younger, less trained and lower-performing counterparts [19-21, 56, 58].…”
Section: Individualizationmentioning
confidence: 99%
“…Previous research has indicated that there is not only variability in the physiological response to different approaches to POR training (e.g., high-volume vs. high-intensity) (Fry and Kraemer, 1997 ; Bell et al, 2020 ; Grandou et al, 2020b ), but that differences might also occur in a group of individual athletes undertaking the same training protocol. These differences are likely to be modulated by multiple factors including genotype (Clarkson et al, 2005 ), sex differences (Hunter, 2016 ) muscle fiber typology (Bellinger et al, 2020 ; Lievens et al, 2020 ), age, and biological maturation (Moran et al, 2017 ). Additional factors such as level of competition/status (elite vs. non-elite) (Kreher and Schwartz, 2012 ) and the athlete's “stress capacity” (i.e., the ability to tolerate the combined effects of training and non-training stressors) (Kenttä and Hassmén, 1998 ; Stults-Kolehmainen and Bartholomew, 2012 ) are also likely to play a role in the response to POR.…”
Section: Discussionmentioning
confidence: 99%